On the combination of the critical distance theory with a multiaxial fatigue criterion for predicting the fatigue strength of notched and plain shot-peened parts. (December 2016) - Benedetti, M.; Fontanari, V.; Allahkarami, M.; Hanan, J.C.; Bandini, M.
Highlights: Notched and plain specimens subjected to controlled shot peening. Residual stresses measured along the notch bisector. Reconstruction of initial and stabilized residual stresses. Residual and stress field averaged over a critical area. The size of the critical area is independent of the loading ratio. Abstract: Predicting the effect of shot peening on the fatigue life is not an easy task, since it depends on a variety of influence parameters, among them: surface roughness, residual stresses distribution in the peened component and their evolution throughout the service-life, location of the crack initiation site. Indeed, in our experience, preferential crack initiation sites are localized close to the notch root in notched samples and near to edges in prismatic plain specimens. Moreover, the site of crack initiation tends to move sub-superficially with increasing fatigue lifetime. In view of these observations, we believe that a fatigue design method shall take into account the actual external and residual stress field in the neighbourhood of the crack initiation site. For this reason, we suggest using the critical distance theory in the form of an area method to average the stress field in this critical location. Through a numerical/experimental technique, we have estimated the stress field produced by surface peening dimples as well as the residual stress field in the vicinity of sharp edges and notch roots. Stresses were incorporated into a multiaxial fatigue criterion for predicting the S-N curves of peened notched and plain samples made of Al-7075-T651 alloy.